Limits of Freedom of Public Authorities with Respect to Obtaining Evidence at the Stage of Investigation : A Comparative Legal Study - Rogacka-Rzewnicka, Maria, (International Law E-Books Online, Collection 2025., 2024)
Any democratic legal system recognizes that the pursuit of the truth about a crime must have impassable limits, and that in contemporary legal systems the public authorities' principle of freedom to obtain evidence in criminal proceedings is not absolute. Drawing these boundaries is a permanent process, which produces universal legal problems of fundamental practical importance. This book addresses the fundamental importance of the protection of the individual from potential actions of state bodies that violate legally marked boundaries. Contributors synthesize knowledge about the admissibility of evidence in criminal procedure, evidence that must not be used or should not be used under certain circumstances, and the conditions for the admissibility of unlawfully obtained evidence. This comparative analysis of national evidentiary procedures is an essential showcase of certain legislative patterns and similarities between individual legal systems. See Less